Rhegmatogenous retinal detachment with a giant tear located in the intermediate periphery: Two case reports. Issue 4 (January 2019) - Kohmoto, Ryohsuke; Fukumoto, Masanori; Sato, Takaki; Oosuka, Shou; Kobayashi, Takatoshi; Kida, Teruyo; Suzuki, Hiroyuki; Ikeda, Tsunehiko
Abstract: Rationale: We experienced 2 cases of retinal detachment (RD) with giant tears located in the intermediate periphery of the fundus. In this case report, we investigated the clinical characteristics in these 2 cases. Patient concerns and diagnoses: Case 1 involved a 63-year-old male, who became aware of metamorphopsia and decreased visual acuity (VA) in his left eye. Upon examination, he was diagnosed with a giant tear at the margin of the intermediate peripheral lattice degeneration. Case 2 involved a 54-year-old male, who became aware of decreased VA in his right eye. Upon examination, he was diagnosed with vitreous hemorrhage and a giant tear located in the upper intermediate periphery. In these 2 cases, there was no obvious previous or familial history. Interventions: In both cases, reattachment was achieved by performing vitrectomies. Outcomes: These 2 cases were characterized by the refraction being close to emmetropia due to the flat corneal curvature, even though there was a long axial length and the eyeballs were spherically large. In both cases, the postoperative clinical course outcome was favorable and no complication occurred Lessons: Our findings indicate that intermediate peripheral giant tears may occur in spherically large eyeballs, and that vitreous surgery is effective in such cases. Since the risk of the onset of RD in the fellow eye is thought to be high, strict postoperative follow-up is necessary.